Investigations on torsion of the two-chords single laced members = Badania na skręcanie dwugałęziowych prętów stalowych skratowanych w jednej płaszczyźnie - Lorkowski, Paweł; Gosowski, Bronisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents experimental and numerical studies to determine the equivalent second moment of area of the uniform torsion of the two-chord steel single laced members. The members are used as poles of railway traction network gates, and steel columns of framed buildings as well. The stiffness of uniform torsion of this kind of columns allows to the determine the critical loads of the spatial stability.
Keywords: steel structures; two-chords member; single laced member; torsion; experimental investigation; numerical investigation; konstrukcje stalowe; element dwugałęziowy; elementy skratowane; pojedyncza płaszczyzna skratowań; skręcanie; badania doświadczalne; badania numeryczne